Development of a High-Efficiency Immunomagnetic Enrichment Method for Detection of Human Norovirus via PAMAM Dendrimer/SA-Biotin Mediated Cascade-Amplification - Gao, Junshan; Zhang, Le; Xue, Liang; Cai, Weicheng; Qin, Zhiwei; Yang, Jiale; Liang, Yanhui; Wang, Linping; Chen, Moutong; Ye, Qinghua; Li, Ying; Wang, Juan; et al. (Frontiers in Microbiology, 2021)
Human norovirus is a common cause of acute gastroenteritis worldwide, and oysters have been found to be the main carriers for its spread. The lack of efficient pretreatment methods has been a major bottleneck limiting the detection of viruses in oysters. In this study, we established a novel immunomagnetic enrichment method using polyamidoamine (PAMAM) dendrimer/SA-biotin-mediated cascade amplification for for reverse transcriptase quantitative real-time polymerase chain reaction (RT-qPCR) detection. We compared the capture efficiency of traditional immunomagnetic enrichment, biotin-amplified immunomagnetic enrichment, and PAMAM dendrimer/SA-biotin-mediated cascade-amplification immunomagnetic enrichment. The optimal capture efficiency of the novel method was 44.26% ± 1.45%, which increased by 183.17% and 18.09% compared with the first two methods, respectively. The three methods were used to detect norovirus in 44 retail oysters. The detection rate of the PAMAM dendrimer/SA-biotin-mediated method was 25.0%, which was higher than that of the other two methods by 6.2% and 9.1%, respectively. This study aimed to reduce the economic cost, time, and increase the detection rate. This method can be applied for the rapid detection of norovirus in oysters.